Hubungan Faktor Risiko Penyakit Jantung Koroner dengan Insidens Kejadian Kardiovaskular Mayor pada Pasien STEMI yang Menjalani IKP Primer di RSUP Prof Dr. R. D. Kandou Manado Periode Januari - Desember 2022 - Toliu, Feiby C.; Joseph, Victor F. F.; Rampengan, Starry H. (Universitas Sam Ratulangi, 2025)
Abstract: Major adverse cardiovascular events (MACE) are adverse outcomes in ST elevation myocardial infarction (STEMI) patients, such as death, recurrent myocardial infarction, stroke, rehospitalization, and recurrent revascularization. The occurrence of MACE depends on the patient's age, gender, and lifestyle. This study aimed to determine the relationship between coronary heart disease risk factors and the incidence of MACE in STEMI patients undergoing primary PCI (PPCI). Samples were STEMI patients undergoing PPCI at Prof. Dr. R. D. Kandou Hospital, from January to December 2022. This was a retrospective cohort study using the consecutive sampling method. Data were analyzed using the chi-square test and Fisher's exact test. The results obtained 169 cases STEMI patients undergoing PPCI; 80 of them fulfilled the inclusion criteria. The majority of patients did not experience MACE. The most common type of MACE was rehospitalization. The bivariate analysis, it showed that there was no significant relationship between coronary heart disease risk factors and MACE in STEMI patients undergoing PPCI. In conclusion, there is no significant relationship between coronary heart disease risk factors and major adverse cardiovascular events. Keywords: major adverse cardiovascular events; coronary heart disease; risk factors Abstrak: Kejadian kardiovaskular mayor (KKM) merupakan hasil akhir yang merugikan pada pasien dengan ST elevation myocardial infarction (STEMI), berupa kematian, infark miokard berulang, stroke, rehospitalisasi, dan revaskularisasi berulang. Terjadinya KKM bergantung pada usia, jenis kelamin, dan faktor gaya hidup pasien. Penelitian ini bertujuan untuk mengetahui hubungan antara faktor risiko penyakit jantung koroner dengan insidens KKM pada pasien STEMI. Sampel penelitian ialah pasien STEMI yang menjalani IKP Primer di RSUP Prof. Dr. R. D. Kandou Manado periode Januari - Desember 2022. Jenis penelitian ialah cohort retrospektif dengan metode consecutive sampling. Uji statistik ialah analisis univariat dan analisis bivariat menggunakan uji chi square dan uji Fisher’s exact. Hasil penelitian mendapatkan 169 penderita STEMI yang menjalani IKP primer dengan 80 sampel yang memenuhi kriteria inklusi. Sebagian besar pasien tidak mengalami KKM. Jenis KKM yang paling banyak ditemukan ialah rehospitalisasi. Berdasarkan analisis bivariat, tidak didapatkan hubungan bermakna antara faktor risiko penyakit jantung koroner dengan kejadian kardiovaskular mayor pada pasien STEMI yang menjalani IKP Primer. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara faktor risiko penyakit jantung koroner dengan kejadian kardiovaskular mayor. Kata kunci: kejadian kardiovaskular mayor; penyakit jantung coroner; faktor risiko